726 Extravasation in children. (17th August 2022) - Battersby, Alex; Slack, James; Armstrong, Alice; Fraser, Catriona; Unsworth, Sarah; Ollett, Louise; Lewis, Christopher
Abstract : Aims: Extravasation is a rare but serious complication of IV (intravenous) therapy. It can cause pain, tendon/nerve damage, infection, and in severe cases, tissue necrosis. 1 There is a lack of data on the incidence of paediatric extravasation injuries, but estimates vary between 0.01 and 7%. 2 As extravasation is rare, junior doctors may not be aware of the potential severity. In response to a significant extravasation we decided to review our practice about cannula management and guidance about extravasation on paediatric wards. We aimed to review our practice and look for ways to reduce the frequency of extravasation and improve the recognition and management of extravasation in children outside of the oncology unit. Methods: 1. We performed an audit of paediatric wards to see if cannula insertion was documented as per hospital guideline 2. We reviewed 'datix' of extravasation injuries in patients under 16 years of age (excluding neonates) to see if there were common factors 3. We designed a new management of extravasation guideline and provided education about this guideline ( figure 1 ). Results: 30% of the 28 cannulated inpatients had a complete record of their cannula insertion and 64% had documented inspections of their cannula site. 90 Datix records 51 excluded as under neonatal team 9 omitted due to no documented evidence of an injury 13 were found to have had another adverse event relating to IV infusion (allergic or transfusion reaction) likely demonstrating poor clinical coding of extravasation injuries. Of the remaining 15 patients, 73% had an extravasation event involving a cannula (27% involved a central line). In 26% of cases, the injury was either discussed with or reviewed by plastics. 86% were managed conservatively. 1 patient required theatre for line removal. 1 patient required debridement and skin grafting. 40% had communication difficulties We created a 'how to guide' to educate professional about how to document cannula insertion Conclusion: Documentation of IV cannula insertion was far below the 100% expected. We identified that the process was complicated and have created a how to guide, which is in the departmental handbook and will be discussed at induction. We will re-audit this. We identified high risk groups from the historical cases of extravasation and have highlighted these in our new guideline. We did not have an up to date guideline for extravasation outside of the oncology department and felt this was needed. The guideline was created alongside the plastic surgical team allowing us to be clear about the need for their early intervention. We continue to provide an ongoing education programme to nursing and medical staff about the importance of prevention, recognition and treatment of extravasation. References: Corbett M, Marshall D, Harden M, Oddie S, Phillips R, McGuire W. Treatment of extravasation injuries in infants and young children: a scoping review and survey. Health Technol Assess 2018;22(46). Pérez Fidalgo JA, García Fabregat L, Cervantes A, Margulies A, Vidall C, Roila F, ESMO Guidelines Working Group. Management of chemotherapy extravasation: ESMO-EONS Clinical Practice Guidelines. Ann Oncol 2012;23(Suppl. 7):vii167–73.